SIMPLE DRONE FOR OBJECT COLOR DETECTION - Abdulrazzaq Jabbar, Malik (Journal of Engineering and Sustainable Development, 2017)
Multirotor unmanned aerial vehicles (UAVs), such as quadcopters and hexacopters, have become increasingly popular in recent years. This is due to their capability to hover along with other specifications that make them viable in many applications. In this work, the development and integration of a quad-copter in X-configuration with an IP camera for object detection based on the color of an object are handled. A KK2 microcontroller is used to control the quadcopter movements. The controller has built-in gyros that provide heading rate information, which is used to control the movement of the quadcopter. The parts of the whole UAV are selected and integrated. The calibration processes are handled after installing the necessary controller codes. This is to make the quadcopter fly according to set commands and smoothly. The IP camera is integrated with a quadcopter frame to acquire images of objects to detect a pre-specified target color. A mobile camera with GPS data is used here for the detection. Two algorithms were next implemented to acquire and analyze the images received from the IP camera. The results show that the images were captured and analyzed successfully and the objects were remotely detected based on their color. As a result, the developed algorithms can be used as a part in remote observation systems.